An integrated organic–inorganic geochemical characterization of Paleogene sediments in No.1 Structural Belt of the Nanpu Sag, Bohai Bay Basin, eastern China: implications for the origin of organic matter. Issue 1 (2020) - Guo, Yu; Gang, Wenzhe; Gao, Gang; Yang, Shangru; Jiang, Chong; Chen, Guo; Zhu, Chuanzhen; Li, Xiaofeng; Wang, Yifan; Dong, Yuexia; Goldberg, Karin
No abstract available